The Pengembangan Media Papan Lingkaran Satuan Trigonometri Untuk Memudahkan Siswa Memahami Konsep Perbandingan Trigonometri - Nursidrati; Sofyan Syamratulangi; Edi Firmansyah (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2023)
This research is classified as development research to develop trigonometry unit circle learning media to help students understand the concept of trigonometry comparisons in class X students. The problem in this research is that students always experience difficulties in understanding trigonometry concepts. The type of research used is R&D research or development research. The research procedures carried out are analyzing the product to be developed, the initial development of the product, and finally conducting product trials. In product validation, the results obtained were 3.45 which showed that the trigonometry unit circle learning media was included in the valid category. Meanwhile, in the product trial, the results of the student questionnaire were 3.44 indicating that the trigonometry unit circle media is a practical category so that the trigonometry unit circle board learning media can make it easier for students to understand the concept of trigonometry